2004
DOI: 10.1016/j.spl.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics in the symmetrization inequality

Abstract: We give a sufficient condition for i.i.d. random variables X 1 , X 2 in order to have P {X 1 − X 2 > x} ∼ P {|X 1 | > x} as x → ∞. A factorization property for subexponential distributions is used in the proof. In a subsequent paper the results will be applied to model fragility of financial markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The defining relation is again (1.4). Subexponential distributions on the real line were studied before by Willekens [40], Omey [31] and Geluk [16].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The defining relation is again (1.4). Subexponential distributions on the real line were studied before by Willekens [40], Omey [31] and Geluk [16].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The first Lemma (see [16]) shows that it is sufficient to study the behaviour of nonnegative random variables under maxima and convolutions. The next Lemma is well known (see e.g.…”
Section: Weighted Sums Of Iid Random Variables In Smentioning
confidence: 99%
“…Part (a) is a combination of Lemma 1 of Geluk [12] and Lemma 4.2 of Ng et al [25], while part (b) can be found in Embrechts and Goldie [8]. To prove part (c), note that, by part (a), the relation…”
Section: Heavy-tailed Distributionsmentioning
confidence: 88%
“…The convolution closure of S is from [7]. The other results of parts (ii) and (iii) are from [11] and [10], respectively.…”
Section: Then the Asymptotic Relations In (13) Holdmentioning
confidence: 99%
“…for random variables on the real line; see, e.g. [10], [15], and [22]. For background information on subexponentiality and its applications, the reader is referred to [2], [4], [8], [18].…”
Section: Introductionmentioning
confidence: 99%